2015
DOI: 10.1182/blood-2015-05-645424
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil oxidative burst activates ATM to regulate cytokine production and apoptosis

Abstract: Key Points Activation of ATM kinase modulates neutrophil functions and is dependent on the oxidative burst. Neutrophils from ataxia telangiectasia patients overproduce inflammatory cytokines and have a prolonged lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 52 publications
1
55
1
2
Order By: Relevance
“…Both cell types lacked DNA-PK CS protein expression; however, unlike in monocytes the DNA damage response kinases ATR and ATM were also not detectable in neutrophilic granulocytes. This contrasts with a previous report where ATM was activated and pATM was detected after IR or PMA treatment [30]. Furthermore, the DSB marker γH2AX was also not detectable in dose- and time-response experiments after treatment with IR, which is compatible with the observed lack of DNA damage-dependent kinases in our samples.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Both cell types lacked DNA-PK CS protein expression; however, unlike in monocytes the DNA damage response kinases ATR and ATM were also not detectable in neutrophilic granulocytes. This contrasts with a previous report where ATM was activated and pATM was detected after IR or PMA treatment [30]. Furthermore, the DSB marker γH2AX was also not detectable in dose- and time-response experiments after treatment with IR, which is compatible with the observed lack of DNA damage-dependent kinases in our samples.…”
Section: Discussioncontrasting
confidence: 57%
“…It was also reported that PMA-treated blood cells displayed phosphorylation of ATM and H2AX in granulocytes, monocytes and lymphocytes [29]. Another study found phosphorylated ATM and H2AX (γH2AX) in neutrophils after NADPH oxidase activation and IR [30]. In view of these rather controversial results we analysed DNA repair protein expression and DNA repair capacity in granulocytes after exposure to ROS and IR.…”
Section: Discussionmentioning
confidence: 99%
“…7A), and observed an increase as previously reported by Harbort et al [32]. In addition KU-55933, a specific inhibitor of ATM decreased the phospho-ATM of neutrophils in a concentration dependent way (Fig.…”
Section: Resultssupporting
confidence: 88%
“…It has recently been reported that stimulated neutrophils generate a burst of ROS that induce DNA damage signaling in activated neutrophils and macrophages, suppressing cytokine production and inducing apoptosis. If the DNA damage reparative systems are effective cells will survive, otherwise they will become apoptotic and die [35][36][37].…”
Section: Cellular Apoptosis Induction and Regulation Pathwaysmentioning
confidence: 99%